Cesarean Section Rates and Adverse Neonatal Outcomes After Induction of Labour Versus Expectant Management in Women With an Unripe Cervix: A Secondary Analysis of the HYPITAT and DIGITAT Trials. Issue 2 (June 2017) - Bernardes, T.P.; Broekhuijsen, K.; Koopmans, C.M.; Boers, K.E.; van Wyk, L.; Tajik, P.; van Pampus, M.G.; Scherjon, S.A.; Mol, B.W.; Franssen, M.T.; van den Berg, P.P.; Groen, H.
Abstract : ( BJOG . 2016;123(9):1501–1508) Between 20% and 25% of pregnancies involve induction of labor (IOL), with the intervention indicated when conditions exist where a better outcome for mother and/or child would be expected if the pregnancy is not further prolonged. However, the effectiveness of IOL is debatable, especially in the setting of an unripe cervix, with studies indicating an associated high rate of cesarean section (CS). The objective of this study was to evaluate CS and adverse neonatal outcome rates for IOL versus expectant management in women with an unripe cervix at or near term, using a secondary analysis of data from 2 previously completed randomized trials.